EVALUASI INPUT DALAM IMPLEMENTASI PROGRAM ANJUNGAN DUKCAPIL MANDIRI (ADM) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BANDAR LAMPUNG - Juniarni, Nisrina Alifah; Mulyana, Nana; Apandi, Apandi (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2025)
Digital transformation in public services has become a pressing need in the modern era, particularly in the field of population administration. The Anjungan Dukcapil Mandiri (ADM) program represents a strategic innovation by Indonesia’s Ministry of Home Affairs aimed at enabling citizens to independently print civil registration documents, thereby reducing reliance on conventional bureaucratic services. This study evaluates the input aspect of ADM implementation in Bandar Lampung City using the CIPP (Context, Input, Process, Product) evaluation model, focusing on regulatory readiness, human resource capabilities, infrastructure availability, and budget support. A descriptive qualitative approach was employed, involving in-depth interviews, direct observation, and document analysis. The findings reveal that despite the existence of national-level regulatory support, implementation at the regional level is hampered by the absence of local technical Standard Operating Procedures (SOPs), limited availability of ADM machines, inadequate technical training for operators, and insufficient public outreach. These input constraints directly affect the program’s ability to function efficiently and equitably across the population. The study concludes that the success of ADM as a digital service innovation relies heavily on the quality and sufficiency of input resources. Strategic interventions are necessary, including the expansion of ADM units, capacity-building for service personnel, and the formulation of an inclusive and sustainable public communication strategy to enhance public engagement and service utilization.